Sodium levels for Japanese quail at initial phases - Costa, F. G. P.; Figueiredo-Lima, D. F.; Lima, M. R.; Pinheiro, S. G.; Goulart, C. C.; Silva, J. H. V.; Baraldi-Artoni, Silvana Martinez [UNESP]; Barreiro, F. R. [UNESP]; Givisiez, P. E. N. (Poultry Science Assoc Inc, 2012)
The aim of this research was to determine the nutritional requirements of sodium for Japanese quail (Coturnix coturnix Japonica) during the periods of 1 to 21 d and 22 to 40 d of age, as well as to evaluate the residual effect on egg production and densitometry bone traits from 41 to 63 d. Two experiments were developed. Experiment 1: 360 Japanese quail were used, from 1 to 21 d of age. Treatments consisted of 5 sodium levels (0.06, 0.12, 0.18, 0.24, and 0.30%). Experiment 2: 240 Japanese quail were used, from 22 to 40 d. Treatments consisted of 5 sodium levels (0.04, 0.12, 0.20, 0.28, and 0.36%). In both experiments, weight gain, final weight, and feed conversion presented a quadratic trend, whereas water intake presented a linear trend. Treatments did not affect the densitometry of bone traits, although they presented a quadratic influence on tibia ash, calcium, and calcium: phosphorus ratio. Therefore, the nutritional requirement of sodium for Japanese quail from 1 to 21 d and from 22 to 40 d is 0.222% and 0.253%, respectively.
Keywords: bone trait; Coturnix coturnix japonica; Growth; Mineral; nutritional requirement